Hair Tourniquet Syndrome - Amir, Saeed; Ahmad, Munir; Sadiq, Muzzafarudin (Journal of Postgraduate Medical Institute, 2013)
Objective: To find out the causes and sites involved of hair tourniquet syndrome in our setup. Methodology: This descriptive study was conducted in Surgical units of Agency Headquarter Hospital,Landikotal and Govt. City Hospital, Peshawar from 2007-2011. Fifty consecutive cases of hair tourniquet syndrome of both sexes were included. Data was collected on a pre designed proforma regarding thepatient's age, sex, family background, socio-economic status and possible causes of this unique entity byinterviewing the parents, relatives, spiritual healers, paramedical staff and quacks. Site involved was determinedby clinical examinations in the OPD, ward and in operation theatre under sedation. Data was analyzed using SPSS version 16. Results: Out of 50, 38(76%) were male and 12(24%) were female. In 30(60%) patients, glans penis wereinvolved, while other parts involved were digits (hand and foot) in 12%, skin tags in 11(22%), umbilical hernia in 2(4%), meningocele in 1(2%). In 28(56%) cases, no cause was found, especially in infants. Other causes were for the management of nocturia in 12%, amputation of skin tags in 10% and post circumcision bleeding, spiritual healing and jealousy each in 6% patients. Human hair was found in cases of infants and children while in adults animal hair was used. Conclusion: Outcome of Unnoticed and missed hair coils around skin appendages can be devastating inshape of strangulation and amputation whether the cause is known or not.